Dynamische Tests des urethralen Verschlussmechanismus und Beckenbodens - Zmrhal, J; Horcicka, L; Lochman, P (Zentralblatt fur Gynakologie, 2001)
In the group of stress incontinent women (n = 54) the values of cough leak point pressure (CLPP) and Valsalva leak point pressure (VLPP) were studied together with urethral stress profiles. So as to evaluate the function of the pelvic floor during stress manoeuvers the electromyographic potentials were simultaneously recorded. It was verified, that the values of CLPP were significantly increased in comparison with VLPP (p < 0.01), while electromyographic potentials obtained by CLPP test were more powerful than those recorded by VLPP (p < 0.01-p < 0.005) in different subgroups. According to the results mentioned above it can be concluded, that the reaction of the pelvic floor differs significantly due to various stress manoeuvers, like coughing, Valsalva etc. These findings should be considered in evaluation of the type of dysfunction and of the appropriate surgical treatment.
Keywords: Valsalvův manévr; Urethra; pánevní dno; Valsalva Maneuver; Middle Aged; urodynamika; Adult; Pelvic Floor; Cough; uretra; ženské pohlaví; stresová inkontinence moči; Humans; elektromyografie; Electromyography; lidé středního věku; Urodynamics; kašel; dospělí; Urinary Incontinence, Stress; Female; lidé